Konsistensi dan Dinamika Metodologis Tafsir Bintu al-Syāṭi’ dalam Menafsirkan Surah al-Insyirah - Miftahul Jannah; Achmad Abu Bakar; Muhsin Mahfudz (AR ROSYAD: Jurnal Keislaman dan Sosial Humaniora, 2026)
This study aims to analyze the application of Bintu al-Syāṭi’s exegetical methodology in Surah al-Insyirah and to reveal the patterns of its application that emerge in the exegetical process. The research question in this study is: What is the form and degree of consistency of Bintu al-Syāṭi’s methodology in interpreting this surah? This study is qualitative in nature and employs a literature review (library research) approach. The primary reference source is the book *al-Tafsīr al-Bayān li Al-Qur’ān al-Karīm*, supplemented by secondary references from relevant books and journals. The results of the study indicate that Bintu al-Syāṭi’ consistently applies four methodological principles inherited from Amin al-Khullī. However, this consistency is not realized through a linear workflow. In the practice of exegesis, she uses these methodological tools flexibly according to the needs of the verse analysis. This finding indicates that Bintu al-Syāṭi’s methodology is integrative and dynamic, rather than procedural.